2023
DOI: 10.1186/s12912-023-01189-w
|View full text |Cite
|
Sign up to set email alerts
|

Using a simulation-based approach to promote structured and interactive nursing clinical handover: a pre- and post-evaluation pilot study in bilingual Hong Kong

Abstract: Effective clinical nursing handover involves the transfer of responsibility and accountability for patient care between nurses, leading to better patient safety and continuity of care. Nurses in bilingual contexts, such as Hong Kong – where nurses are trained in English but communicate in Cantonese – may find it challenging to deliver a safe clinical handover. This article reports a pilot study in which a simulation-based approach is being developed to enhance nursing handover with structured and interactive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…After conducting the simulation-based training, nurses reported that they carried out the clinical handover with more confidence and that this approach led them to have more structured and interactive clinical handovers. Overall, it was indicated that nurses’ communication significantly improved during the handover [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…After conducting the simulation-based training, nurses reported that they carried out the clinical handover with more confidence and that this approach led them to have more structured and interactive clinical handovers. Overall, it was indicated that nurses’ communication significantly improved during the handover [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to confirm reliability included using a structured nursing handover observation tool when recording observations, checking verbatim transcripts for accuracy and, for the linguistic analysis, discussing informational and interactional categories with the research team. Pre‐post studies have validated the use of the ISBAR and CARE protocols to improve nursing handover (Pun, 2023; Slade et al., 2018), and the training has been adapted in nursing trials to improve patient safety (Liu et al., 2023; Rihari‐Thomas et al., 2022). The study is reported in line with the Standards for Reporting Qualitative Research (O'Brien et al., 2014) and the Consolidated Criteria for Reporting Qualitative Research (Tong et al., 2007) (Appendix S7).…”
Section: Methodsmentioning
confidence: 99%
“…The National Acute Medicine Proggramme mengusulkan agar ISBAR digunakan sebagai model yang digunakan semua staf layanan kesehatan untuk menyusun komunikasi klinis. Sturktur komunikasi ISBAR merupakan adaptasi dari SBAR, sebuah sistem yang dikembangkan oleh Angkatan Laut Amerika Serikat (AS) untuk memastikan komunikasi yang jelas dan tepat antara kapal selam nuklir (Bergess et al, 2020) dan mulai diadopsi oleh layanan kesehatan masyarakat pada tahun 2000-an (17). Sejak ISBAR diperkenalkan, beberapa penelitian menunjukkan adanya peningkatan dalam hal kerja sama, komunikasi, dan keselamatan pasien (9,18).…”
Section: Pembahasanunclassified